Dynamics of a competing two-strain SIS epidemic model with general infection force on complex networks. (June 2021) - Cheng, Xinxin; Wang, Yi; Huang, Gang
Abstract: Most diseases have multiple pathogenic strains, which may impose difficulty in combatting the disease and lead to rich dynamics. However, their dynamical properties are not well understood. For this purpose, we formulate and analyze a two-strain SIS epidemic model with a competing mechanism and general infection force on complex networks. We derive the basic reproduction number and introduce the invasion reproduction numbers for each strain. We demonstrate that if R 0 < 1, the disease-free equilibrium is globally asymptotically stable, i.e., the disease will die out. If R 0 > 1, the conditions of the existence and global asymptotical stability of dominant equilibria are further studied. The persistence of the system is also addressed. Numerical simulations are given to illustrate the theoretical results.